Soature Test of ZPT Onion Extract and Combination of Plant Media on the Growth of Grape (Vitis vinifera l.) Cuttings: Uji Perendaman ZPT Ekstrak Bawang Merah dan Kombinasi Media Tanam Terhadap Pertumbuhan Stek Anggur (vitis vinifera l.) - Yusrony, Mochamad Ilham; Nurmalasari, Intan Rohma (Procedia of Engineering and Life Science, 2023)
Grapes are vines in the form of bushes and or are eaten directly. Grapes contain many polypheno and reseveratrol compounds which are active in various metabolisms, and are able to prevent the formation of cancer cells and other diseases. The main problem with penetrating is that it is difficult to form roots. Therefore, efforts that can be made to encourage, accelerate and stimulate the formation of roots and increase the quality and number of roots can be done by giving PGR to cuttings. This study aims to determine the effect of giving several concentrations of shallot extract and a combination of planting media on the growth of grape cuttings (Vitis vinifera L.) This research was carried out experimentally using a factorial Randomized Block Design (RBD) method with 2 treatment factors consisting of: the first is without soaking natural ZPT, namely K0 = 0% shallot extract, and soaking with natural ZPT, namely K1 = 100% shallot extract. The second factor is the planting medium with 4 levels, namely M1 = Soil; M2 = Soil + Sand (2 : 1); M3 = Soil + Cocopeat + Sand (2 : 1 : 1). From the research results obtained, there was an interaction on the number of shoots at the age of 28 HST, the speed of shoot growth, and the length of the shoots at the ages of 21 and 28 HST.